Download presentation
Presentation is loading. Please wait.
1
Using Fundamental Identities
Objectives: Recognize and write the fundamental trigonometric identities Use the fundamental trigonometric identities to evaluate trigonometric functions, simplify trigonometric expressions, and rewrite trigonometric expressions
2
Fundamental Identities
3
Fundamental Trigonometric Identities
Pythagorean Identities
4
Simplify an Expression
Simplify cot x cos x + sin x. Click for answer.
5
Example: Simplify 1. Factor csc x out of the expression.
6
2. Use Pythagorean identities to simplify the expression in the parentheses.
7
3. Use Reciprocal identities to simplify the expression.
8
Simplifying a Trigonometric Expression
9
Factoring Trigonometric Expressions
Factor the same way you would factor any quadratic. If it helps replace the “trig” word with x Factor the same way you would factor
10
Make it an easier problem.
Let a = csc x 2a2 – 7a + 6 (2a – 3)(a – 2) Now substitute csc x for a.
11
Factoring Trigonometric Expressions
12
Adding Trigonometric Expressions (Common Denominator)
13
Fundamental Identities
14
Simplifying Trigonometric Expressions
Claim: Proof:
15
4.2 Verifying Trigonometric Identities
Verifying identities Testing identities using a graphing calculator
16
Verifying Identities Verify right-to-left:
17
Verifying Identities Using a Calculator
Graph both sides of the equation in the same viewing window. If they produce different graphs they are not identities. If they appear the same the identity must still be verified. Example:
18
Basic Trigonometric Identities
In this powerpoint, we will use trig identities to verify and prove equations
28
c) tan x sin x + cos x = sec x
Proving an Identity Prove the following: a) sec x(1 + cos x) = 1 + sec x = sec x + sec x cos x = sec x + 1 1 + sec x L.S. = R.S. b) sec x = tan x csc x c) tan x sin x + cos x = sec x L.S. = R.S. L.S. = R.S. 5.4.8
29
= (sin2x - cos2x)(sin2x + cos2x) = (1 - cos2x - cos2x) = 1 - 2cos2x
Proving an Identity d) sin4x - cos4x = cos2 x = (sin2x - cos2x)(sin2x + cos2x) = (1 - cos2x - cos2x) = 1 - 2cos2x 1 - 2cos2x L.S. = R.S. e) L.S. = R.S. 5.4.9
30
Proving an Identity f) L.S. = R.S. 5.4.10
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.